(untitled) (DA NANG JOURNAL OF MEDICINE AND PHARMACY, 2026)
Objectives: To describe the clinical and paraclinical characteristics of the group of subjects undergoing surgery and to initially evaluate the effectiveness and safety of the plasma knife tonsillectomy method in the local area. Methods: A cross-sectional descriptive study with analysis on 131 pediatric patients (aged 3 to under 16 years) who were indicated for tonsillectomy using a plasma knife. Data on surgery duration, blood loss, pain level (VAS score), complications, and length of hospital stay were collected and analyzed. Results: The mean operative time was 18.4 ± 5.0 minutes, with minimal blood loss (4.7 ± 1.8 mL). Postoperative pain scores significantly decreased from day 1 (6.6) to day 7 (0.95). The complication rate was 1.5%, with no late complications reported. The mean length of hospital stay was 2.8 days. Conclusion: Preliminary research shows that tonsillectomy using plasma knife results in shorter intervention time, less blood loss, and quicker pain relief post-surgery. The results recorded a low complication rate, initially demonstrating the feasibility and safety of implementing this technique at local healthcare facilities.